Chitosan-based defluorination composite material and preparation method thereof
By using chitosan-based fluorine removal composite materials, loading lanthanum or aluminum metal salts to form a porous structure, the problems of low adsorption capacity and high cost of existing fluorine adsorption technologies are solved, and efficient and economical fluorine ion adsorption and regeneration are achieved.
Patent Information
- Application Number
- CN202510291339.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
AI Technical Summary
The existing fluorine adsorption technology has problems such as low adsorption capacity, high cost, and complex activation and regeneration processes, making it difficult to effectively remove fluorine ions.
Chitosan-based fluorine-depleting composite material is used, which is supported by chitosan and is supported by lanthanum or aluminum metal salts. It forms a porous structure through the treatment of acetic acid solution and aqueous ammonia solution to improve adsorption performance.
It has achieved efficient adsorption of fluorine ions, with an adsorption capacity of up to 49.6 mg/g, a fast adsorption rate, good renewability and low cost.
Smart Images

Figure CN119793414A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a chitosan-based fluorine removal composite material and a preparation method thereof, and belongs to the technical field of water treatment. Background Art
[0002] Fluoride is highly toxic and bioaccumulative. Once it enters the ecosystem, it will not only pollute the water body, but also endanger human health through the food chain. At present, industrial wastewater discharge implements the first-level fluoride discharge standard of ≤10.0mg / L in the "Comprehensive Wastewater Discharge Standard" (GB8978-1996). Long-term drinking of water with a fluoride concentration of 1.5-4mg / L may cause dental fluorosis, which is manifested as white spots or stripes on the teeth; long-term exposure to 4-10mg / L, in addition to more serious dental fluorosis, may also cause bone fluorosis. Bone fluorosis is manifested as hardening of bones, formation of bone spurs, and joint pain and stiffness, affecting normal movement ability. Therefore, the "Surface Water Environmental Quality Standard" (GB3838-2002) of the receiving water body requires that the fluoride discharge standard of Class I, II, and III water quality is ≤1.0mg / L.
[0003] Traditional fluorine adsorption technology has disadvantages such as low adsorption capacity, high cost, and complex activation and regeneration processes. This urgently requires finding a new adsorbent that can efficiently adsorb fluorine while having good regeneration performance. Summary of the invention
[0004] In view of the problems of low adsorption capacity, complex renewability and high cost of existing fluorine adsorbents, the present invention provides a chitosan-based fluorine removal composite material and a preparation method thereof, which has good adsorption performance, good renewability and low cost.
[0005] In order to achieve the above object, the present invention adopts a chitosan-based fluorine removal composite material, which includes chitosan as a carrier and a metal salt loaded on the chitosan; the metal salt is a lanthanum metal salt, or a lanthanum metal salt and an aluminum metal salt.
[0006] As an improvement, chitosan is used as a skeleton carrier, and the metal salt is loaded on the chitosan.
[0007] As an improvement, the lanthanum metal salt is lanthanum chloride or lanthanum nitrate.
[0008] As an improvement, the aluminum metal salt is aluminum chloride or aluminum nitrate.
[0009] The second aspect of the present invention also provides a method for preparing the chitosan-based fluorine removal composite material, comprising the following steps:
[0010] S1. Dissolve chitosan fully in acetic acid solution and stir to form a uniform and viscous chitosan liquid;
[0011] S2, slowly pouring the metal salt solution into the chitosan solution, fully reacting and mixing, to form a chitosan metal mixed solution; the metal salt solution is a lanthanum metal salt solution, or a mixture of a lanthanum metal salt solution and an aluminum metal salt solution;
[0012] S3, slowly dripping the chitosan metal mixed solution into the ammonia solution to form white gel-like chitosan metal particles;
[0013] S4. Wash the white gel-like chitosan metal particles and dry them to form a chitosan-based fluorine removal composite material.
[0014] As an improvement, in step S1, a chitosan solution with a mass concentration of 3-10% is fully dissolved in an acetic acid solution with a volume concentration of 3-10%, and stirred to form a uniform and viscous chitosan liquid.
[0015] As an improvement, in step S2, a lanthanum metal salt solution with a concentration of 0.3-0.5 mol / L and an aluminum metal salt solution with a concentration of 0-0.2 mol / L are stirred and mixed, and slowly poured into the chitosan solution to react and mix evenly to form a chitosan metal mixed solution.
[0016] As an improvement, the volume concentration of the ammonia solution in step S3 is 40-60%.
[0017] The third aspect of the present invention also provides an application of a chitosan-based defluorination composite material in defluorination of sewage, the chitosan-based defluorination composite material being prepared by the chitosan-based defluorination composite material or the preparation method.
[0018] As an improvement, 0.2 g of the chitosan-based fluoride removal composite material is added into 100 ml of a fluoride ion solution having a concentration of 10-120 mg / L and stirred.
[0019] Mechanism of the present invention:
[0020] The present invention forms a porous microstructure during the preparation process. When lanthanum and aluminum components are introduced, pores are generated inside the material to increase the specific surface area. These pores are of different sizes, ranging from micropores to mesopores, providing more channels and active sites for the adsorption of fluoride ions, making it easier for them to contact the adsorbent surface, thereby increasing the adsorption capacity; the metal ions of lanthanum and aluminum can coordinate with functional groups such as amino groups and hydroxyls on chitosan molecules, changing the electron cloud distribution and surface chemical properties of chitosan, thereby generating more active sites, which have a stronger affinity for fluoride ions and can specifically bind to fluoride ions through electrostatic attraction, ion exchange, etc., thereby enhancing the adsorption capacity. The composite of lanthanum, aluminum and chitosan may cause changes in the lattice structure of the material, generating lattice defects and vacancies, which can serve as adsorption sites for fluoride ions, and due to its special chemical environment, the adsorption of fluoride ions has higher selectivity and stability, further improving the adsorption performance.
[0021] Compared with the prior art, the chitosan-based fluorine removal composite material of the present invention has the following beneficial effects:
[0022] (1) Large adsorption capacity. Compared with most of the currently synthesized defluorination adsorbent materials, under the same conditions, the adsorption capacity of the chitosan-based defluorination composite material of the present invention can reach 49.6 mg / g, which is 1.5-2 times the adsorption capacity of most of the currently synthesized defluorination adsorbent materials.
[0023] (2) The adsorption rate is fast. When the adsorption time reaches 100 minutes, it is basically close to the saturated adsorption capacity, which is more than twice the adsorption rate of the resin currently in use.
[0024] (3) The regeneration method is simple. The adsorption saturated chitosan-based defluorination composite material is placed in deionized water and ultrasonicated. The regeneration efficiency is higher than 90%.
[0025] (4) The adsorption lower limit is low. 0.2 g of chitosan-based fluoride removal composite material can reduce the initial fluoride ion concentration of 100 ml of solution with an initial concentration of 20 mg / L to 0.02 mg / L within 10 min, and the removal efficiency can reach 99.9%.
[0026] (5) Green and mild, the reaction is carried out at room temperature and pressure. The chitosan required for the reaction is the product of removing some acetyl groups from the natural polysaccharide chitin. It is biodegradable, biocompatible and non-toxic. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a graph showing the variation of the fluoride ion adsorption amount of the chitosan-based fluoride removal composite material of Example 1 of the present invention over time;
[0028] Figure 2This is a graph showing the variation of the adsorption capacity of the chitosan-based fluorine removal composite material according to Example 1 of the present invention with the number of regeneration times. DETAILED DESCRIPTION
[0029] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention.
[0030] Example 1
[0031] A method for preparing a chitosan-based fluorine removal composite material comprises the following steps:
[0032] (1) Dissolve 5 ml of acetic acid in 70 ml of water, then dissolve 5 g of chitosan in 25 ml of water, slowly drop the mixed chitosan solution into the acetic acid solution and titrate to 100 ml. Stir for 1 hour while slowly dropping the chitosan solution into the acetic acid solution to ensure complete mixing.
[0033] (2) Pour 146.21 g of lanthanum nitrate into a volumetric flask, add a small amount of deionized water to dissolve the solute, shake until dissolved, add water to the 1 L mark to obtain a 0.45 mol / L lanthanum nitrate solution. Pour 6.68 g of aluminum chloride into a volumetric flask, add a small amount of deionized water to dissolve the solute, shake until dissolved, add water to the 1 L mark to obtain a 0.05 mol / L aluminum chloride solution. Take 100 ml of each and mix the two for 15 minutes to mix them evenly.
[0034] (3) adding the mixed solution obtained in step (2) to the solution obtained in step (1), stirring for 1 hour to mix them evenly to form a chitosan lanthanum aluminum mixed solution;
[0035] (4) dripping the chitosan lanthanum aluminum mixed solution obtained in step (3) dropwise into a 50% ammonia solution to form white gel particles, which were filtered and washed;
[0036] (5) The white gel-like particles obtained in step (4) were placed in an oven at 100° C. and dried for 4.5 h to obtain a chitosan-based fluorine removal composite material.
[0037] The defluorination performance of the chitosan-based defluorination composite material prepared in Example 1 was tested:
[0038] 0.2g chitosan-based fluoride removal composite material was added to 100mL of fluoride ion solution with initial concentration of 10, 20, 40, 60, and 120mg / L, respectively. After magnetic stirring for 4 hours, the fluoride ion concentration in the solution was measured using a fluoride ion electrode. The fluoride ion concentration was measured to be reduced to 0.01, 0.01, 0.03, 0.17, and 20.6 mg / L, respectively;
[0039] Then, 0.2 g of the chitosan-based fluoride removal composite material was placed in 100 ml of a fluoride ion solution with a concentration of 120 mg / L. The fluoride ion concentrations were measured by a fluoride ion selective electrode at 10 min, 20 min, 30 min, 45 min, 60 min, and 240 min, respectively, and the results were 67.8, 52.8, 41.4, 33.4, 26.4, and 20.8 mg / L, and the corresponding fluoride adsorption amounts were 26.4, 33.6, 39.3, 43.3, 46.8, and 49.6 mg / g. Figure 1 As shown;
[0040] 0.2 g of chitosan-based fluoride removal composite material was added to 100 mL of fluoride ion solution with an initial concentration of 120 mg / L. After magnetic stirring for 4 h, the fluoride ion concentration in the solution was measured using a fluoride ion electrode, and then regenerated with deionized water. This was repeated 5 times. The adsorption capacity was measured to be 49, 48.3, 47.3, 46.1, and 44.8 mg / g, respectively, with the increase of the number of regenerations. The regeneration efficiency was greater than 90% each time. Figure 2 shown.
[0041] Example 2
[0042] A method for preparing a chitosan-based fluorine removal composite material comprises the following steps:
[0043] (1) Dissolve 5 ml of acetic acid in 70 ml of water, then dissolve 5 g of chitosan in 25 ml of water, slowly drop the mixed chitosan solution into the acetic acid solution and titrate to 100 ml. Stir for 1 hour while slowly dropping the chitosan solution into the acetic acid solution to ensure complete mixing;
[0044] (2) Pour 129.96g of lanthanum nitrate into a volumetric flask, add a small amount of deionized water to dissolve the solute, shake until dissolved, add water to the 1L mark to obtain a 0.40mol / L lanthanum nitrate solution. Pour 13.36g of aluminum chloride into a volumetric flask, add a small amount of deionized water to dissolve the solute, shake until dissolved, add water to the 1L mark to obtain a 0.10mol / L aluminum chloride solution. Take 100ml of each and mix the two for 20min to mix them evenly.
[0045] (3) adding the mixed solution obtained in step (2) to the solution obtained in step (1), stirring for 1 hour to mix them evenly to form a chitosan lanthanum aluminum mixed solution;
[0046] (4) dripping the chitosan lanthanum aluminum mixed solution obtained in step (3) dropwise into a 50% ammonia solution to form white gel particles, which were filtered and washed;
[0047] (5) The white gel-like particles obtained in step (4) were placed in an oven at 100° C. and dried for 5 h to obtain a chitosan-based fluorine removal composite material.
[0048] Example 3
[0049] A method for preparing a chitosan-based fluorine removal composite material comprises the following steps:
[0050] (1) Dissolve 5 ml of acetic acid in 70 ml of water, then dissolve 5 g of chitosan in 25 ml of water, slowly drop the mixed chitosan solution into the acetic acid solution and titrate to 100 ml. Stir for 1 hour while slowly dropping the chitosan solution into the acetic acid solution to ensure complete mixing;
[0051] (2) Pour 129.96 g of lanthanum nitrate into a volumetric flask, add a small amount of deionized water to dissolve the solute, shake until dissolved, and add water to the 1 L mark to obtain a 0.40 mol / L lanthanum nitrate solution;
[0052] (3) adding 100 ml of the lanthanum nitrate solution obtained in step (2) to the solution obtained in step (1), stirring for 1 hour to mix them evenly to form a chitosan-lanthanum mixed solution;
[0053] (4) dripping the chitosan-lanthanum mixed solution obtained in step (3) dropwise into a 50% ammonia solution to form white gel particles, which were filtered and washed;
[0054] (5) The white gel-like particles obtained in step (4) were placed in an oven at 100° C. and dried for 5 h to obtain a chitosan-based fluorine removal composite material.
[0055] The chitosan-based fluorine removal composite material of the present invention has good selectivity and good adsorption performance for fluorine ions, as well as excellent recycling and regeneration ability. The chitosan-based fluorine removal composite material has high adsorption capacity for fluorine ions and is highly efficient and stable.
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A chitosan-based fluorine removal composite material, characterized in that: The invention comprises chitosan as a carrier and a metal salt loaded on the chitosan; the metal salt is a lanthanum metal salt, or a lanthanum metal salt and an aluminum metal salt.
2. The chitosan-based fluorine removal composite material according to claim 1, characterized in that: Chitosan is used as a skeleton carrier, and the metal salt is loaded on the chitosan.
3. The chitosan-based fluorine removal composite material according to claim 1, characterized in that: The lanthanum metal salt is lanthanum chloride or lanthanum nitrate.
4. The chitosan-based fluorine removal composite material according to claim 1, characterized in that: The aluminum metal salt is aluminum chloride or aluminum nitrate.
5. A method for preparing the chitosan-based fluorine removal composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Dissolve chitosan fully in acetic acid solution and stir to form a uniform and viscous chitosan liquid; S2, slowly pouring the metal salt solution into the chitosan solution, fully reacting and mixing, to form a chitosan metal mixed solution; the metal salt solution is a lanthanum metal salt solution, or a mixture of a lanthanum metal salt solution and an aluminum metal salt solution; S3, slowly dripping the chitosan metal mixed solution into the ammonia solution to form white gel-like chitosan metal particles; S4. Wash the white gel-like chitosan metal particles and dry them to form a chitosan-based fluorine removal composite material.
6. The method for preparing a chitosan-based fluorine removal composite material according to claim 5, characterized in that: In the step S1, a chitosan solution with a mass concentration of 3-10% is fully dissolved in an acetic acid solution with a volume concentration of 3-10%, and stirred to form a uniform and viscous chitosan liquid.
7. The method for preparing a chitosan-based fluorine removal composite material according to claim 5, characterized in that: In the step S2, a lanthanum metal salt solution with a concentration of 0.3-0.5 mol / L and an aluminum metal salt solution with a concentration of 0-0.2 mol / L are stirred and mixed, and slowly poured into the chitosan solution to react and mix evenly to form a chitosan metal mixed solution.
8. The method for preparing a chitosan-based fluorine removal composite material according to claim 5, characterized in that: The volume concentration of the ammonia solution in step S3 is 40-60%.
9. Application of a chitosan-based defluorination composite material in wastewater defluorination, characterized in that: The chitosan-based fluorine-removal composite material is prepared by the chitosan-based fluorine-removal composite material according to any one of claims 1 to 4 or the preparation method according to any one of claims 5 to 8.
10. The use according to claim 9, characterized in that: 0.2 g of the chitosan-based fluoride removal composite material was added into 100 ml of a fluoride ion solution having a concentration of 10-120 mg / L and stirred.
Citation Information
Patent Citations
Iron modified chitosan defluorinated particle adsorbent and preparation method thereof
CN104069830A
Lanthanum aluminum composite metal pillared montmorillonite fluorine-removing adsorbent and preparation method thereof
CN106824062A
Preparation method of millimeter-scale aluminum-lanthanum composite hydroxide gel ball adsorbent and application thereof
CN113952920A
Ultramicroporous carbon material prepared from chitosan, preparation method of ultramicroporous carbon material and method for high-selectivity separation of small molecular hydrocarbon
CN116116389A
Crosslinked chitosan and preparation method thereof, fluorine removal agent and fluorine-containing wastewater adsorption method
CN118652452A